The poem "La Calle" by Octavio Paz through discourse analysis (Orkopata. Revista de Lingüística, Literatura y Arte, 2023)
Octavio Paz's poetry manages to capture the human essence and goes further, dazzling with its beauty and depth. In this context, the purpose of this research was to carry out a critical analysis of the poem "La Calle" by the aforementioned poet. For this purpose, the hermeneutic approach was used as a methodological design and as an interpretation technique the discourse analysis model was applied, covering its textual, enunciative, semiotic and pragmatic dimensions. It is concluded that the poem "La Calle" reflects the atmosphere and environment of a society impacted by a social event, where the street becomes a mysterious and lonely scene, where dreams are intertwined with a reality, where it evokes a sensation of the time stopped in the immediate past.
Keywords: analysis; discourse; ethnography; hermeneutics; linguistics